2023
DOI: 10.1200/jco.22.00628
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II, Two-Stage Study of Letrozole and Abemaciclib in Estrogen Receptor–Positive Recurrent Endometrial Cancer

Abstract: PURPOSE Estrogen receptor (ER)–positive endometrial cancers (ECs) are characterized by phosphatidylinositol 3-kinase (PI3K) and receptor tyrosine kinase (RTK)/RAS/β-catenin (CTNNB1) pathway alterations in approximately 90% and 80% of cases, respectively. Extensive cross-talk between ER, PI3K, and RTK/RAS/CTNNB1 pathways leads to both ligand-dependent and ligand-independent ER transcriptional activity as well as upregulation of cyclin D1 which, in complex with cyclin-dependent kinases 4 and 6 (CDK4 and CDK6), i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…The median duration of response was 7.4 months. The most common serious adverse events were due to bone marrow suppression [ 24 ]. A third randomized phase II trial by the NSGO has been presented but not yet published.…”
Section: Aromatase Inhibitors Combined With Targeted Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The median duration of response was 7.4 months. The most common serious adverse events were due to bone marrow suppression [ 24 ]. A third randomized phase II trial by the NSGO has been presented but not yet published.…”
Section: Aromatase Inhibitors Combined With Targeted Therapiesmentioning
confidence: 99%
“…The investigators observed responses in the trial regardless of grade, prior hormonal therapy, mismatch repair, and progesterone receptor status (all patients had ER expression by trial design). When evaluating responses based on molecular subtypes, they found responses in all subtypes except in the copy-number high (p53 abnormal) group and recommended future studies to further evaluate possible predictors of response, such as mutations of CTNNB1, KRAS, and CDKN2A [ 24 ].…”
Section: Biomarkers Of Response To Hormonal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…47 More recently, a phase II study of letrozole plus abemaciclib in estrogen receptor-positive recurrent/persistent endometrial cancer found a 30% ORR (95% CI 14.7% to 49.4%). 48 Hormonal therapy plus cyclin-dependent kinase 4/6 inhibitors need further evaluation in phase III trials.…”
Section: Nsmp/cnlmentioning
confidence: 99%
“…Multiple clinical trials about palbociclib treated in various tumors such as breast cancer, ovarian cancer, Pancreatic Ductal Adenocarcinoma. Besides, other CDK4/6 inhibitors such as Abemaciclib [ 170 ], Ribociclib [ 171 ], Lerociclib [ 172 ], Trilaciclib [ 173 ], Dinaciclib [ 174 ], and SHR6390 [ 175 ] are also being adopted in clinical testing.…”
Section: Cdk4/6 Inhibitorsmentioning
confidence: 99%